Figurazioni del Demone del racconto in César Aira e dintorni (Altre Modernità, 2017)
Cesar Aira has become a significant presence in contemporary Argentine literature, and not only in terms of influence on the younger generation of Latin American novelists. The figure of himself as Author has taken on the form of a character in his novels, which are by no means necessarily autobiographical. The Aira character may exist independently of him (Aira the Author), by appearing in the works of other writers and thereby transforming him into a true storybook hero. One of Aira’s latest books, Entre los indios (2012), focuses on the character of the Devil as the Narrator, a sort of mythological figure at the origins of narration itself. Is this an ironic inversion of Benjamin's thesis, according to which the Storyteller is the figure in which the righteous man encounters himself? Anyhow, in Entre los indios the Devil seems to have lost his power and he’s just looking for a bit of reality…